Four Vertex-Degree-Based Topological Indices of VC\(_5\)C\(_7[p;q]\) Nanotubes - Jamil, Muhammad K.; Javed, Aisha; Nazeer, Waqas; Farahani, Mohammad R.; Gao, Yingying (Communications in Mathematics and Applications, 2017)
Recently, I. Gutman et al. presented four vertex-degree based graph invariants, that earlier have been considered in the chemical and/or mathematical literature, but, that evaded the attention of most mathematical chemists. These are the reciprocal RandiÄ‡ index (RR), the reduced reciprocal RandiÄ‡ index (RRR), the reduced second Zagreb index (RM\(_2\)) and the forgotten index (F). In this article, we compute these indices of VC\(_5\)C\(_7[p;q]\) Nanotubes.